Polynomials and Taylor’s Approximations - Tuladhar, Nhuchhe Shova (Journal of the Institute of Engineering, 2017)
The main objective of this article is to make a formal description of the polynomial, polynomial equations with definitions and their properties. Besides studying some of its uses in real life situations, we shall discuss polynomial approximation using higher order derivatives. Journal of the Institute of Engineering, 2016, 12(1): 214-221